2019
DOI: 10.7150/thno.31159
|View full text |Cite
|
Sign up to set email alerts
|

Cuboidal tethered cyclodextrin frameworks tailored for hemostasis and injured vessel targeting

Abstract: Rationale : Targeted delivery of therapeutic drugs or imaging agents to injured blood vessels via nanocarriers is likely to be dependent on the particle shape, yet cubic nanoparticle carriers have not been reported for vascular targeting. Here, we demonstrate that cuboidal cyclodextrin frameworks possess superior hemostasis effect and injured vessels targeting compared with spherical counterpart. Methods : Cuboidal and biocompatible γ-cyclodextrin metal-organic frameworks (CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…[34] Recently, we functionalized cubic crosslinked γ-CD-MOFs with GRGDS pentapeptides to construct efficient artificial platelets for bleeding control. [35] Our results proved that the unique cuboidal shape of CD-MOFs plays an important role in achieving hemostasis and in vivo targeting of artificial platelets. Porous γ-CD-MOFs were also utilized as templates to synthesize ultrafine silver nanoparticles (Ag NPs) by our group.…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…[34] Recently, we functionalized cubic crosslinked γ-CD-MOFs with GRGDS pentapeptides to construct efficient artificial platelets for bleeding control. [35] Our results proved that the unique cuboidal shape of CD-MOFs plays an important role in achieving hemostasis and in vivo targeting of artificial platelets. Porous γ-CD-MOFs were also utilized as templates to synthesize ultrafine silver nanoparticles (Ag NPs) by our group.…”
Section: Introductionsupporting
confidence: 59%
“…According to our previously reported strategy, the GRGDS pentapeptide was covalently adducted onto the CDF surface (RGD‐CDF) via an ester bond. [ 35 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Holzer et al have shown that carbon-based nanomaterials could induce thrombus formation in rodents independently of their shape (25). In contrast, He et al have recently demonstrated that cuboidal cyclodextrin frameworks enhanced platelet aggregation when compared with their spherical counterpart (26).…”
Section: Introductionmentioning
confidence: 91%